Kekuatan Hukum Register Dati Sebagai Alat Bukti Terhadap Penguasaan Dan Pemilikan Hak Atas Tanah - Fatihatul Mujahid Rafsanjani Pontoh; Jenny Kristiana Matuankotta; Novyta Uktolseja (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: Customary law communities recognize customary land as ulayat land. Purposes of the Research: The purpose of this study is to find out and explain the legal power of the data register as evidence against the control and ownership of land rights.Methods of the Research: The method used in this study is a normative juridical method with a statutory approach, a conceptual approach and a case approach. The legal materials used are primary, secondary and tertiary legal materials. The legal material is analyzed qualitatively in order to answer the problems studied.Results of the Research: Based on the results of the study, it shows that the position of the dati register is as evidence of legal ownership of land rights for the dati community belonging to the customary law community. The dati register provides and guarantees a legal certainty for customary law community groups over dati land. Because it has a position that can be equated with legal evidence of rights to land rights, then dati has binding legal force on the control and ownership of rights to land rights. Therefore, in the settlement of a case related to the land of the dati, the judge may refer to or make the register of the dati as evidence of ownership of the rights to the land of the dati.